2016
DOI: 10.1007/s00134-016-4325-4
|View full text |Cite
|
Sign up to set email alerts
|

The standard of care of patients with ARDS: ventilatory settings and rescue therapies for refractory hypoxemia

Abstract: Purpose: Severe ARDS is often associated with refractory hypoxemia, and early identification and treatment of hypoxemia is mandatory. For the management of severe ARDS ventilator settings, positioning therapy, infection control, and supportive measures are essential to improve survival. Methods and results:A precise definition of life-threating hypoxemia is not identified. Typical clinical determinations are: arterial partial pressure of oxygen < 60 mmHg and/or arterial oxygenation < 88 % and/or the ratio of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
143
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(154 citation statements)
references
References 91 publications
(92 reference statements)
2
143
0
9
Order By: Relevance
“…Ordinary infection, burns and septicemia are factors with a high risk of inducing ARDS, and this disease may be fatal if patients are not treated with highly effective therapy (11). A survey indicated that the mortality rate of ARDS may be up to 50% (12) and therefore, the timely administration of effective treatment is important to reduce ARDS-associated fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…Ordinary infection, burns and septicemia are factors with a high risk of inducing ARDS, and this disease may be fatal if patients are not treated with highly effective therapy (11). A survey indicated that the mortality rate of ARDS may be up to 50% (12) and therefore, the timely administration of effective treatment is important to reduce ARDS-associated fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the length of stay at ICU until death or discharge, the occurrence of critical events [hypoxemia (SpO 2 <85% for at least 5 min), hypoglycemia (defined as blood glucose measurement <70 mg/dL), accidental extubation, re-intubation] was assessed. In the clinical intensive care setting, an arterial SpO 2 <85%, corresponding to a PaO 2 ≤50 mmHg with a time span of a few minutes, is accepted as a valuable marker for hypoxemia (16,17). The advocated measures in these situations are the control of artificial airways and ventilator function/modes/settings, the suction of endotracheal secretions, the acute use of open lung approaches, and/or acute imaging diagnostics (Chest X-ray, ultrasound).…”
Section: Measures and Data Collectionmentioning
confidence: 99%
“…As the intensive care community gains more and more knowledge of what measures induce and worsen ventilator induced lung injury (VILI), lung-protective ventilation strategies become a conditio sine qua non (26). On the same lines, non-invasive ventilation has advanced to be an easy to use and effective way to bridge a phase of respiratory failure for many patients.…”
mentioning
confidence: 99%